Absence of the Musculocutaneous Nerve and Associated Compensation by the Median Nerve - Moore, K.; Prasad, A. M.; Badagabettu, S. N. (Kathmandu University Medical Journal, 2020)
The musculocutaneous and median nerves frequently show variations from their normal course. The purpose of this paper is to report a rare variation, in which the right musculocutaneous nerve was absent. Consequently, the median nerve supplied motor innervation to the flexor compartment of the arm and sensory innervation to the lateral aspect of the forearm. The primary targets of this paper are orthopedic surgeons, anesthesiologists and radiologists. In cases of injuries to the upper limb, knowledge of these variations can assist them in avoiding misdiagnoses.